Is gravitational search algorithm's initial gravitational constant a function dependent parameter? - Nor Azlina, Ab. Aziz Nor; Hidayati, Abdul Aziz; Aminurafiuddin, Zulkifli; Zuwairie, Ibrahim; Tasiransurini, Ab. Rahman (Association for Computing Machinery, 2018)
Gravitational search algorithm (GSA) has several parameters to be initialized. One of the parameter is the initial gravitational constant G0. In the original GSA G0 is initialized to 100. Here, the robustness of this setting is evaluated using several test functions. The value of G0 is varied between 10 to 100000. The results from the experiment are statistically compared. It is found that G0 is a function dependent parameter and its original value is not a robust setting.